Early Robotic-Assisted Laparoscopic Pyeloplasty for Infants Under 3 Months With Severe Ureteropelvic Junction Obstruction - Li, Pin; Zhou, Huixia; Cao, Hualin; Guo, Tao; Zhu, Weiwei; Zhao, Yang; Tao, Tian; Zhou, Xiaoguang; Ma, Lifei; Yang, Yunjie; Feng, Zhichun (Frontiers in Pediatrics, 2021)
Objective To present our primary experience of robotic-assisted laparoscopic pyeloplasty (RALP) for severe ureteropelvis junction obstruction (UPJO) infants under 3 months. Methods We performed a retrospective study of 9 infants under 3 months who underwent RALP for severe UPJO between April 2017 and March 2019 in our center. The severe UPJO was defined as infants with severe hydronephrosis (Society of Fetal Urology grades III or IV , anteroposterior diameter＞3 cm or split renal function <40% or T 1/2 ＞20 min) involving bilateral, solitary kidney or contralateral renal hypoplasia UPJO at the same time. All the clinical and perioperative and postoperative information were collected. Results There were four bilateral UPJO cases, two solitary kidney UPJO cases and three unilateral UPJO with contralateral renal hypoplasia cases included. All of the infants were undertaken RALP by one single surgeon. The mean age of the infants was 1.62 ± 0.54 months. The mean operative time was 109.55±10.47 min. The mean estimated blood loss was 19.29 ± 3.19 ml and the mean length of hospital stay was 5.57±0.73 days. According to the ultrasonography results, all patients have a significant recovery of renal function at 12 months after the operation. Conclusions To maximize the protection of renal function, early RALP is a safe and feasible option for the treatment of severe UPJO infants under 3 months.